Antileishmanial Activity of 2-Phenoxy Nicotinic Acid Hydrazide Sulfonamide against Leishmania (L) Major [MRHO/IR/75/ER] Promastigotes: An In-Vitro Study - Parisa Kianfar (Journal of Global Pharma Technology, 2017)
Introduction: cutaneous leishmaniasis is parasitic disease in Iran and a major health problem in the country. The aim of this study was to compare the efficacy-achieved derivatives of 2-phenoxy nicotinic acid hydrazide sulfonamide and glucantime is in the treatment of leishmaniasis. Material and method: In this experimental- laboratory study Leishmania major promastigotes, a standard strain MRHO / IR / 75 / ER were cultured in NNN medium. Then in tubes containing medium, 105 Leishmania (equivalently100 ml) and 0.5 ml of dilution of 2-phenoxy nicotinic acid hydrazide sulfonamide and glucantime at a concentration of 2/0, 1, 5, 25 and 125 µg/ml separately added. Cell proliferation assay done by using BrdU (XTT) kit. Result: The results of variance analysis showed that 2-phenoxy nicotinic acid hydrazide sulfonamide derivatives and Glucantime have inhibitory effect on the parasite Leishmania. all concentrations tested 2.0, 1, 5, 25 and 125 µg/ml decreased the number of Leishmania parasites that their effects compared to control group was statistically significant (P = 0.000). Conclusion: 2-phenoxy nicotinic acid hydrazide sulfonamide derivatives able to inhibit the in vitro proliferation of Leishmania major and compared to Glucantime had better inhibitory effect on major promastigotes growth of Iranian rural leishmaniasis. Keywords: 2-phenoxy nicotinic acid hydrazide sulfonamide, Leishmania major, Glucantime, promastigotes.